Teaching Literature Using Interactive Powerpoint Presentation for Grade 8 Students at Banisil National High School - ARSAD, HAKIMA; Mangindra, Anesa (International Journal of Arts, Sciences and Education, 2025)
As technology continues to advance, integrating modern tools into education becomes essential to enhance students' learning experiences. This study examined the effectiveness of interactive PowerPoint presentations as a teaching strategy for literature and analyzed their impact on students' academic performance. The study aimed to assess the effects of using interactive PowerPoint presentations on students' literature learning. It involved two groups of students—the experimental and control groups. At the beginning of the study, a pre-test was conducted to measure their initial level of learning, where both groups failed to meet the expected proficiency level. By the end of the experiment, findings revealed that the experimental group, which utilized interactive PowerPoint presentations, achieved a higher mean score in the final test compared to the control group. Statistical analysis showed a significant difference in the mean gain scores of both groups, indicating the positive impact of interactive PowerPoint presentations. Interactive elements such as animations, visual aids, and other engaging activities contributed to improving students' comprehension and skills. Based on the results, interactive PowerPoint presentations proved to be an effective teaching method that enhances learning quality and expands students' proficiency in using technology. However, the intervention's effectiveness may be influenced by factors such as teachers' technological literacy and students' readiness to engage with digital tools. These limitations should be considered to further improve the implementation of innovative teaching strategies.